Modern Pulse Corticosteroid Therapy in Patients with Multiple Sclerosis: Adverse Events and Clinical and Pharmacological Measures to Eliminate Them - Chernenko, Maksym; Nehreba, Tetiana; Voloshyna, Nataliya; Vasylovskyy, Vitaliy; Pohulaieva, Tetiana (SSP Modern Pharmacy and Medicine, 2025)
Pulse therapy with methylprednisolone remains the standard treatment for exacerbations of multiple sclerosis. The appointment of corticosteroids can cause several undesirable phenomena and complications, one of which is the development of steroid myopathy and pronounced general weakness. To reduce the expressiveness of these violations, metacartin was used. The study included 57 patients with a reliable diagnosis of multiple sclerosis at the stage of exacerbation of the pathological process. There were 32 (56.14%) patients with the relapsing-remitting course of multiple sclerosis, and 25 (43.85%) with the secondary-progressive course. All patients were randomly divided into two groups: I – 33 (80.83%) patients who underwent a course of pulse therapy with methylprednisolone followed by the introduction of metacartin, and II – 24 (19.17%) patients who received only pulse therapy with methylprednisolone therapy. Group I included 23 patients with relapsing-remitting course and 10 patients with secondary-progressive course multiple sclerosis. 15 patients with relapsing-remitting course and 9 patients with secondary-progressive course multiple sclerosis was included in the II group. The study showed the effectiveness of combination of pulse-therapy with methylprednisolone and the metacartin, the prescription of which reliably reduced the severity of "muscular" symptoms when pulse therapy was prescribed.